Impact of Extrusion Cooking Variables on the Nutritional and Sensory Attributes of Rice-Defatted Sesame Breakfast Cereal - Abdulkadir Aliyu Ndabokun; Arise Abimbola Kemisola; Egwumah Ojochenemi Rebecca; Mohammed Alhassan; Shehu Hauwa; Kabaraini Maryam Alfa; Kayode Bukola Idowu; Babagana Mohammed (Journal of Agriculture and Rural Development Studies, 2025)
Cereal-based foods are considered to lower risk to food safety compared to many other foods, which make them the good source of protein, B vitamins, energy and minerals for the general population. Blending rice and defatted sesame would provide a wide range of high protein, calories and micronutrients if properly processed. The retention of these essential nutrients was enhanced through the application of extrusion cooking processes such as barrel temperature, feed moisture content and feed blend composition. Extrusion cooking was carried out at different barrel temperature (80°C, 110°C and 140°C), different feed moisture content of (10%, 20% and 30%) and feed composition of sesame at (10%, 17.5% and 25%) to investigate the effect of extrusion conditions on nine samples with three control of extruded rice. The proximate composition revealed that the highest protein of the extruded breakfast cereals was 20.46% extruded at 110, 20% moisture and 25% feed blend composition of sesame. Functional properties revealed that the highest bulk density was 0.64g/cm3 140°C barrel temperature, 30% moisture and 10% feed blend composition of sesame. Mineral content of the extrudate showed potassium was found to be high at 2.75mg/kg at a 110°C barrel temperature, 20% moisture and 17.5% feed blend composition of sesame and significant at (P< 0.05). Based on the findings, sample B (R75S25T110M10) exhibited best quality among the extrudates in terms of their nutritional qualities, functional properties and sensory attributes. These findings can be adopted in food industry where rice and sesame are their major ingredients for producing extruded breakfast cereal.